Adoção de práticas de intensificação sustentável na olericultura da Serra Fluminense: uma análise a partir dos recursos e capacidades - Leite, Antonio Edson (2019)
Issues related to the sustainability of productive activities have been the subject of many discussions in various sectors. Agriculture is not excluded from this situation, as resource depletion tends to hamper increased production. In order to meet growing demand, it is essential to adopt technologies and practices that minimize the effects of the farm and also increase productivity in the exploited areas. In this context, the concept of sustainable intensification of production emerges. According to this approach, food security in the future depends on the use of practices and technologies to reconcile increased soil fertility, more efficient use of nutrients and increased food supply. Previous research has sought to identify the factors that may lead to the adoption of sustainable intensification practices (PIS) in agriculture, however, few studies have been devoted to this topic within the olericultura. In view of this reality, the present research sought to identify the determinants of the adoption of practices of sustainable intensification in the olericultura based on a theoretical framework based on the View Based on Resources (VBR) and on the dynamic capabilibities. To do so, a survey was carried out with 213 farmers from the mountainous region of Rio de Janeiro, and the data were collected between April and May 2015. The results obtained by the analyzes allowed to identify that the adoption of PIS depends on the strategic choices of the producers in relation to the intended market. However, such choices can only be successful when producers have the necessary production resources, including machinery and equipment, as well as the capabilities built into them. It can also be concluded that the management capabilities stimulated by the strategic choices, from courses and organizational learning, allow a better allocation of resources and the reconfiguration of routines, making possible the adoption of PIS by olericultores.